Inovasi Pembelajaran Penulisan Tesis: Pengembangan Workshop Berbasis AI untuk Mahasiswa Magister PAI STAI Sirojul Falah Bogor - Muhamad Priyatna; Unang Wahidin; Wartono Wartono; Herman Herman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
The utilization of artificial intelligence (AI) in the academic sphere has become an integral element supporting scientific writing efficiency; however, this integration also poses risks of ethical violations and the decline of critical thinking skills. This study aims to develop an AI-based thesis writing workshop model that focuses not only on technical proficiency but also emphasizes the aspect of moral knowing and scientific integrity for Master of Islamic Religious Education (PAI) students at STAI Sirojul Falah Bogor. The method employed is a participatory and hands-on training approach (learning by doing) involving 16 students. The training stages include academic ethics briefings, demonstrations of digital tools such as Mendeley as well as intensive mentoring for independent reference integration practice. The results indicate that the workshop effectively accelerated the thesis writing process through personalized material and efficient literature analysis. Although AI offers convenience, its successful implementation in Islamic education relies heavily on ethical guidance to mitigate plagiarism risks and maintain the depth of spiritual interpretation. This study recommends the necessity of institutional policies regulating AI use based on Islamic values to ensure students' intellectual honesty.